CdSe/CdS Dot‐in‐Rods Nanocrystals Fast Blinking Dynamics. Issue 23 (31st October 2018) - Manceau, M.; Vezzoli, S.; Glorieux, Q.; Giacobino, E.; Carbone, L.; De Vittorio, M.; Hermier, J.‐P.; Bramati, A.
Abstract: Analyzing the autocorrelation function of the fluorescence intensity, we demonstrate that these nanoemitters are characterized by a short value of the mean duration of bright periods (ten to a few hundreds of microseconds). The comparison of the results obtained for samples with different geometries shows that not only the shell thickness is crucial but also the shape of the dot‐in‐rods. Increasing the shell aspect ratio results in shorter bright periods suggesting that surface traps impact the stability of the fluorescence intensity. Abstract : The blinking dynamics of colloidal core‐shell CdSe/CdS dot‐in‐rods is studied in detail at the single particle level.